2023
DOI: 10.3390/su15054435
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Transportation Route Optimization of Cold Chain Container in Time-Varying Network Considering Carbon Emissions

Abstract: To solve the multimodal transport route optimization problem considering carbon emission, the vehicle speed has time-varying characteristics, and the customer has a time window limit. The carbon emission of multimodal transport system is affected by the energy consumption of transport vehicles in the time-varying network. The time-varying network is uncertain, and carbon emissions may continue to rise after a gradual decline. Based on this, this study established the sum of the carbon emission cost, transporta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…Concurrently, [23] delves into the intricacies of the agricultural logistics chain in China, revealing that road congestion contributes to a carbon emission surge of over 20%, thus advocating for route optimization for cold chain containers to mitigate such adverse impacts.…”
Section: Of 18mentioning
confidence: 99%
“…Concurrently, [23] delves into the intricacies of the agricultural logistics chain in China, revealing that road congestion contributes to a carbon emission surge of over 20%, thus advocating for route optimization for cold chain containers to mitigate such adverse impacts.…”
Section: Of 18mentioning
confidence: 99%
“…Carbon emission cost refers to the cold chain lowcarbon logistics and distribution process, vehicle driving fuel consumption and consumption of refrigerant will produce carbon dioxide, and the fuel consumption is related to the vehicle weight and travelling distance [22]. The formula for calculating the carbon emission cost of vehicle travelling fuel consumption is as follows:…”
Section: Cost Of Carbon Emissionsmentioning
confidence: 99%
“…Robust optimization with uncertain demand will increase the total cost of low-carbon multimodal transport due to the pursuit of stability, and the impact of time uncertainty on the total cost is significant and fuzzy. Liu et al [17] mainly studied the transportation route optimization of cold chain containers in multimodal transport systems, and built an optimization model with the sum of carbon emission cost, transportation cost, time window penalty cost, and cold chain cargo damage cost as the objective function. In addition, the Hummingbird Evolutionary Genetic Algorithm was adopted as a solution tool, and it was found that the optimized multimodal transport route could significantly reduce carbon emissions, thereby reducing the impact on the environment.…”
Section: Research On Multimodal Transport Multiparty Collaborationmentioning
confidence: 99%